Gendering the state in the age of globalization : women's movements and state feminism in postindustrial democracies - Haussman, Melissa, 1959-; Sauer, Birgit (Rowman & Littlefield Publishers, 2007)
Gendering the State is a ground-breaking collection of studies that examines the efforts of women in countries all over the world to frame public policy debates on nationally critical issues in gendered terms. The overall study is grouped into three distinct patterns of state change: state downsizing_particularly in social policy areas (Canada, Finland, the Netherlands, the United States, and Spain); expansion of state activities into previously less-regulated areas (Austria, France, Germany, and Sweden); and transformation_often constitutionally based_of representative structures (Australia.